2021
DOI: 10.21203/rs.3.rs-832277/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in Community and Ambulance Care Processes for Out-of-Hospital Cardiac Arrest During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: Bystander cardiopulmonary resuscitation (BCPR) and early defibrillation can double the chance of survival from out-of-hospital sudden cardiac arrest (OHCA). We investigated the effect of COVID-19 on the pre-hospital chain of survival. We searched five bibliographical databases for articles that compared prehospital OHCA care processes during and before the COVID-19 pandemic. Random effects meta-analyses were conducted, and meta-regression with mixed-effect models and subgroup analyses were conducted where appr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(60 reference statements)
0
2
0
1
Order By: Relevance
“…Second, we have not further stratified the patient’s clinical status before PCI. Third, an increase in out-of-hospital cardiac arrest and death was reported in some countries during the early COVID-19 epidemic, [27,28] and this may affect our study results. However, due to the limitation of the data, we could not analyze this in the study.…”
Section: Discussionmentioning
confidence: 90%
“…Second, we have not further stratified the patient’s clinical status before PCI. Third, an increase in out-of-hospital cardiac arrest and death was reported in some countries during the early COVID-19 epidemic, [27,28] and this may affect our study results. However, due to the limitation of the data, we could not analyze this in the study.…”
Section: Discussionmentioning
confidence: 90%
“…E probléma tárgyalása viszont kiemelten fontos, ha nem forgalmas közterületen következik be a keringésmegállás, mert akkor a legtöbb esetben nincs jelen több ellátó. Ezenkívül pedig speciális helyzetként megemlíthető a COVID-19-világjárvány, amelynek során a bevezetett intézkedések miatt kimutathatóan csökkent az OHCA-k észlelése, valamint a megkezdett segítségnyújtások száma [32,33]. E speciális esetekben viszont kompromiszszumot kell kötni: a V-CPR alkalmazásához az okostelefont el kell helyezni, ami késlelteti a mellkaskompressziók megkezdését, vagy rögtön el kell kezdeni az újraélesztést, ezáltal nem élve a V-CPR lehetőségével.…”
Section: A Videoasszisztált úJraélesztés Alkalmazhatóságának Befolyás...unclassified
“…A meta-analysis was conducted to overcome the limitations of individual investigations, and results with implications for OHCA epidemiological features and mortality, which were notably different from those before to the pandemic, were reported. [1] , [2] , [3] , [4] Several observational studies and meta-analyses found that the composition of OHCA patients changed as the number of cardiac arrests increased in COVID-19 patients, where respiratory failure is a somewhat more prevalent cause. In addition, an increase in home arrest due to the effect of social distancing measures and self-quarantine isolation, as well as an influence on the weakening of the chain of survival due to the concentration of medical resources on COVID-19, were shown as an indirect effect.…”
Section: Introductionmentioning
confidence: 99%